(untitled) - Droogers, Peter (Colombo, Sri Lanka, 2002)
This publication will give an overview of the available global datasets on irrigated areas and an evaluation of their strenghts and weaknesses.
Keywords: Irrigation,Water consumption,Geographic information systems; Maps,Maps